Graphene-Si solar cells using 2D hBN monolayer passivation - Mohamed Ashraf Bin Mohamed Abubakar (Nanyang Technological University, 2024)
This project explores the integration of graphene and 2D hexagonal boron nitride (hBN) monolayers in silicon (Si) solar cells to enhance efficiency and stability. Graphene’s high electrical conductivity and transparency, coupled with hBN’s dielectric properties, offer a promising approach to reducing surface recombination losses. The study involves the fabrication of Graphene-Si solar cells with hBN passivation, comparing their performance with other variants, including black graphene, black hBN graphene, and planar graphene.